دور البلوماسية الفلسطينية في مسار تحقيق الاعتراف الكامل في الامم المتحدة - بوخزنة, منار (جامعة الوادي University of Eloued, 2018)
"ملخص الدراسة : عكفت هذه الرسالة على دراسة دور الدبلوماسية الفلسطينية في مسعاها لتحقيق الاعتراف الأممي و نيل العضوية الكاملة في الأمم المتحدة ، إذ أبرزت هذه الدراسة المراحل التاريخية لمحاولات الاستقلال و إعلان الدولة الفلسطينية بداية بإعلان حكومة عموم فلسطين و الدولة الفلسطينية سنة 1948 ، مرورا بقيام منظمة التحرير الفلسطينية في سنة 1964 ، و وصولا إلى إعلان استقلال الدولة الفلسطينية في سنة 1988 ، ثم توقيع اتفاق أوسلو أو ما يسمى أيضا إعلان المبادئ لترتيبات الحكومة الذاتية الفلسطينية ، و الذي وقعت عليه منظمة التحرير الفلسطينية و الكيان الإسرائيلي سنة 1993 ، وما زامن تلك المراحل من اعترافات على مستوى الساحة الدولية ، و القرارات الأممية التي تزامنت مع كل مرحلة . كما عكفت هذه الدراسة على تأكيد الموقف المبدئي للأمم المتحدة من القضية الفلسطينية ، و الذي جددته المنظمة الدولية في قرارها 181 سنة 1948 لإنشاء دولة فلسطينية ، و قررت الجمعية العامة للأمم المتحدة قبول فلسطين عضو مراقب في المنظمة بأغلبية ساحقة من قبل معظم دول العالم ، و ما ترتب عليه من استحقاقات قانونية و سياسية في صالح الدولة الفلسطينية و التي تخدم قضيتها على المستوى الدولي . كما عرضت الدراسة مجموعة من البدائل المتاحة أمام الدبلوماسية الفلسطينية لتعزيز مسعاها لنيل العضوية الكاملة في الأمم المتحدة ، ومن بين هذه البدائل حشد المزيد من الاعترافات الدولية لرفع تمثيلها الدبلوماسي في الأمم المتحدة ، وبديل إعادة تكرار طلب العضوية الكاملة و التوجه إلى مجلس الأمن لأجل استصدار توصية إيجابية منه ، وكبديل ثالث تناولته الدراسة تقديم طلب الانضمام إلى عضوية المحكمة الدولية باعتبارها أهم الأجهزة الرئيسية للأمم المتحدة و لتدعم فرصتها في نيل العضوية الكاملة ، ويعد تفعيل القرار 377 متحدون من أجل السلامUnity For Peace كخيار أخر للدبلوماسية الفلسطينية ، حيث يقف أمام عائق مجلس الأمن الناتج عن التعسف في استخدام الفيتو و حق النقد ، و بالتالي اعتماد دولة فلسطين من دولة مراقب إلى عضو دائم في المنظمة عن طريق الجمعية العامة . كما أسفرت الدراسة على جملة من النتائج تمثلت في : ـ تعدد البدائل و الخيارات الدبلوماسية المتاحة للقيادة الفلسطينية و التي ترتقي من خلالها إلى العضوية الكاملة في الأمم المتحدة . ـ ضرورة تكرار الدبلوماسية الفلسطينية محاولات في استصدار توصية إيجابية أو قرار خاص بالقضية الفلسطينية من قبل مجلس الأمن و الاعتبار من محاولات الدول الأخرى حيث أن جل الدول التي تعثرت عضويتها في السابق تتمتع حاليا بالعضوية الكاملة في الأمم المتحدة و وكالاتها المتخصصة . " "Study Summary This study focused on the role of Palestinian diplomacy in its quest to achieve international recognition and attain full membership in the United Nations. This study highlighted the historical stages of the attempts of independence and the declaration of the Palestinian state beginning with the declaration of the Palestinian government and the Palestinian state in 1948, to the establishment of the Palestine Liberation Organization in 1964, and to the declaration of the independence of the Palestinian state in 1988, and then the signing of the Oslo Agreement or the so-called Declaration of Principles for Palestinian Self-Government Arrangements signed by the Palestine Liberation Organization and the Zionist Entity in 1993, and what coincided with those stages of confessions at the level of the international arena, and the UN resolutions that coincided with each stage. The study also emphasized the initial situation of the United Nations on the Palestinian issue, which was renewed by the international organization in its resolution 181 of 1948 to establish a Palestinian State. The General Assembly of the United Nations decided to accept Palestine as an observer member of the Organization by an overwhelming majority by most countries of the world. Resulting in legal and political entitlements in favor of the Palestinian state and serving its cause at the international level. The study also presented a range of alternatives available to the Palestinian diplomacy to enhance its pursuit of full membership in the United Nations. Among these alternatives is the gatheringof more international recognitions to raise its diplomatic representation in the United Nations, and the alternative of repeating the request for full membership and addressing the Security Council for a positive recommendation. A third alternative is to apply for membership in the International Tribunal as the most important body of the United Nations and to support its chances of full membership. Resolution 377 ,""United for Peace""is another option for the Palestinian diplomacy where it stands in front of the Security Council impediment resulting from the abuse of using Veto and the right of criticism, and therefore the adoption of the State of Palestine from an observer member to a permanent member of the organization through the General Assembly. The study also resulted in a number of conclusions: -The multiplicity of alternatives and the diplomatic options available to the Palestinian leadership through which it will be promoted to full membership in the United Nations. -The need to repeat the attempts for the Palestinian diplomacy to obtain a positive recommendation or a resolution on the Palestinian issue by the Security Council and consideration of the attempts of other countries as most of the countries that have stumbled in the past with the membership, currently have full membership in the United Nations and its specialized agencies. "
انظمة سياسية مقارنة و الحكم الراشد
Keywords: الدبلوماسية، الفلسطينية ، الامم المتحدة; Palestinian diplomacy, the United Nations